PENERAPAN EXPRESSING WRITING DALAM MENINGKATKAN ADVERSITY QUOTIENT PADA ANAK PANTI ASUHAN - Inayah Nabila Abdjul; Adinda Kartika Putri Neoe; Anisa Anisa; Fajriah An. Sabbu; Fatra Adjis; Marya Danisyah Mandagi; Maya Maya; Anik Indarwati (Elsia: Jurnal Psikologi Manusia, 2023)
This study was conducted to determine whether there was an increase in adversity quotient after implementing expressing writing in orphanage children. This research method uses a quantitative research type and uses a pre-experimental design experiment with a pretest-posttest one group design research type. This type of user is imposed on one group only without a comparison group with a total of 30 populations and 14 samples, The results of this study are that the subjects did a pretest with a total value of 104.36 then given treatment and after being given treatment the subjects did a posttest with a total value of 111.29. which means that the subject's AQ increased by 6.7% with a significance of 0.001 <0.05 which means significant.